IMPLEMENTASI KEBIJAKAN PAJAK BUMI DAN BANGUNAN (PBB) DI DINAS PENDAPATAN DAERAH KABUPATEN MAMUJU UTARA - Rahman, Hendra (Katalogis, 2016)
The aim of this study was to determine and analyze the implementation of the policy of Land and Building Tax (PBB) at the Department of Revenue North Mamuju regency. This type of research is qualitative by taking community informants and officials / employees of Department of Revenue North Mamuju regency determined purposively. Data collection methods include participant observation, in-depth interviews, documentation, and triangulation, while the technique of data analysis include data reduction, data is displaydan draw conclusions and verification. The theory in the implementation of land and building tax policy that is a model of public policy implementation raised by George C. Edwards III in Indiahono (2009: 31) there are four important variable in achieving successful implementation of public policy is communication, resources, disposition and bureaucratic structure The results of the study demonstrate policy implementation Land and Building Tax (PBB) in North Mamuju regency already socialized, but the human resources involved in the policy is still lacking and insufficient. besides that it is still a lack of willingness of employees to increase kejenjang higher education, and the budget allocated to the Department of Revenue is still lacking and grossly inadequate. Thus, the factors that most influence the success and failure of policy implementation in the Land and Building Tax Department of Revenue is a factor of resources